A path forward to better space security: Finding new solutions to space debris, space situational awareness and space traffic management. Issue 2 (June 2019) - Pelton, Joseph N.
Abstract: This article addresses the growing problems of space debris elevating the increased risk of orbital collisions as well as the difficulty of accurate space situational awareness, especially with regard to smaller space debris. These problems of space situational awareness (SSA) and space traffic management (STM) will become more acute as perhaps as many as twenty thousand new satellites are deployed in low Earth orbit (LEO) as part of new large scale constellations. This problem will grow as these LEO satellites need to be replaced within a cycle of perhaps every five to seven years . Many believe that there is now a need for space traffic management (STM) capabilities to cope with all these issues. There are no specific agreements, however, on how space traffic management might be systematically accomplished at the international level. The good news is that the Working Group on the Long Term Sustainability of Outer Space Activities (LTSOSA) and COPUOS agreed to 21 new guidelines relating to the longer term sustainability of space and which help to establish a foundation for future efforts to create a process that could aid future space traffic control processes. Several key guidelines which were discussed extensively within the Working Group which could have aided the future prospects for traffic management, however, were not agreed before the Working Group adjourned in June 2018. This article also highlights the problem of space traffic management in near-space or 'protospace'. These concerns grow as there is more activity in the stratosphere due to deployment of high altitude platform systems, more launches through the stratospher to deploy satellite constellation, more de-orbit operations, and perhaps increased operation of spaceplanes and hypersonic transportation in these upper altitude areas not covered by current commercial air traffic management and control. This article not only addresses these types of issues in terms of safety concerns and increased risks, but also suggests new and innovative ways that these concerns might be addressed through regulatory reforms and codification of best practices. These proposals thus outline new ways forward and suggest reforms that could supplement the efforts of the UN Committee on the Peaceful Uses of Outer Space (COPUOS) in its efforts to address these safety and security concerns.